Teacher Professionalization and Training Management: What Job Reference(s) and Professional Skills in a Real Work Situation? - Choukrallah, Mohamed; Bassiri, Mustapha; Belaaouad, Said; Benmokhtar, Said (TECCIENCIA, 2022)
Professionalization seems to have a positive impact in the construction of professional identity, in the sense that its process constitutes a powerful integrative vector for future teachers in the socio-professional context. The study would analyze the constraints that hinder this process of university professionalization at the ENS of Casablanca, among students of the third year "professional license: Teaching of physical education and sports" in a situation of pedagogical internship. Through a quantitative descriptive methodological survey approach based on a questionnaire designed through the literature review, we targeted a sample composed of 120 students - trainees (58% students / 42% students), 30 tutors in internship and 20 trainers. The variables evaluated are the hourly volume of internships, the teaching skills of student-trainees, the coordination between the actors in internships, the supervisory skills of tutors in internships, the modalities of training and socio-professional support. The data is analyzed by an analysis of variance. Our results showed the insufficient hourly volume devoted to the internship and the negative influence of the heterogeneity of skill levels between trainees (intragroup) on socio-professional construction, as well as the lack of coordination between internship actors and the lack of basic skills among trainees and tutors in internship in terms of teaching and supervision that hinders the process of professionalization and collective construction professionalizing. We retain through this study that professionalization is multifactorial in its process of operationalization. It is necessary to overcome all the constraints that hinder this approach for cost-effective and integrative training.